Frequency of zikir (remembrance to Allah) in drug rehabilitation process among Malay society - Adam, Fadzli; Wan Ahmad, Wan Ibrahim; Abd. Fatah, Sudirman (Centre for Promoting Ideas (CPI), 2012)
Drug rehabilitation process has experienced significant transformation from traditional and spiritual approaches to modern and technology based methods.Statistically, numbers of drug addicts, type of drug used and the starting age of using drug among the youths have shown a serious and worrying phenomenon.This study, therefore, seeks to analyze varying frequency of zikir (remembrance to Allah) practice either jahar (aloud) or khafi (silent) of the former drug addicts and a group of relapse.A total of 60 respondents, 30 persons are former drug addicts in Terengganu and another 30 persons are relapsed drug addicts who are on rehabilitation process at the Pondok Remaja Inabah (PRI) Kedah and Terengganu, were involved in this study.Besides, there were also 10 key informants.Data were collected using structured interviews and analyzed using triangulation methods.The results showed a significant difference between the two groups in relation to the frequency of zikir practice.The study found that frequency of zikir among the former drug addicts was higher than of the relapse. Therefore, the frequency level of zikir (remembrance to Allah) is perceived to be one of the important contributing factors to rehabilitate individuals from drug addiction.